Positional Cloning of the Flowering Time QTL qFT12-1 Reveals the Link Between the Clock Related PRR Homolog With Photoperiodic Response in Soybeans - Li, Yuqiu; Dong, Yingshan; Wu, Hongyan; Hu, Bo; Zhai, Hong; Yang, Jiayin; Xia, Zhengjun (Frontiers in Plant Science, 2019)
Flowering time and maturity are important agronomic traits for soybean cultivars to adapt to different latitudes and achieve maximal yield. Genetic studies on genes and quantitative trait loci (QTL) that control flowering time and maturity are extensive. In particular, the molecular bases of E1-E4, E6, E9, E10, and J have been deciphered. For a better understanding of regulation of flowering time gene networks, we need to understand if more molecular factors carrying different biological functions are also involved in the regulation of flowering time in soybeans. We developed a population derived from a cross between a landrace Jilincailihua (male) and a Chinese cultivar Chongnong16 (female). Both parents carry the same genotypes of E1e2E3HaE4 at E1, E2, E3, and E4 loci. Nighty-six individuals of the F2 population were genotyped with Illumina SoySNP8k iSelect BeadChip. A total of 2,407 polymorphic single nucleotide polymorphism (SNP) markers were used to construct a genetic linkage map. One major QTL, qFT12-1, was mapped to an approximately 567-kB region on chromosome 12. Genotyping and phenotyping of recombinant plant whose recombination events were occurring within the QTL region allowed us to narrow down the QTL region to 56.4 kB, in which four genes were annotated. Allelism and association analysis indicated Glyma.12G073900, a PRR7 homolog, is the strongest candidate gene for qFT12-1. The findings of this study disclosed the possible involvement of circadian clock gene in flowering time regulation of soybeans.